Regeneración del mirador del cerro el tablazo en el complejo turístico del cantón Santa Elena - Cedeño Mendoza, Johnny Omar (2018)
The research has a purpose, which is to create and design a proposal not only architectural, but also sustainable in relation to project and environment, giving a possible solution to the problems of tourism, cultural, commercial and recreational present due to the lack of completion of the mirador project located on the hill "El Tablazo". For this type of landscape regeneration of the El Tablazo sector of the Santa Elena canton, the research methodology of standards and design used have criteria of sustainability fulfilling the requirements of the canton that is growing; as a general objective, it is promoted to improve the quality of life both of the inhabitants and of the tourists, this remains as a hierarchical reference in this specific area of study, they are also aligned to the PNBV 2013-2017 objectives…………